1996
DOI: 10.3109/10428199609045720
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-Cell Lymphomas Respond Well to Vincristine, Adriamycin, Cyclophosphamide, Prednisone and Etoposide (VACPE) and Have a Similar Outcome as High-Grade B-Cell Lymphomas

Abstract: Peripheral T-cell lymphomas (PTCL) represent a heterogeneous group of T-cell malignancies including subentities with favourable (large cell anaplastic) or unfavourable (pleomorphic) prognosis. The clinical outcome of PTCL has been controversially discussed, but a worse prognosis than high-grade B-cell Non-Hodgkin's lymphomas (NHL) has been postulated by most authors. In this report we summarize the results of a prospective comparative study investigating the therapy outcome of 27 patients (pts) with PTCL and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
0
22
1
Order By: Relevance
“…4 In a subgroup analysis of patients with PTCLu, although patients with AITL had more advanced disease and less bulky masses than those observed in patients with PTCLu, the other characteristics of these patients were similar. Furthermore, the rates of CR/CRu, OS, PFS, and DFS did not Regarding the effect of immunophenotype on patient outcomes, although some earlier studies that were based on the older classification systems reported similar prognoses between patients with Band T-cell lymphomas, [11][12][13][14] most recent studies consistently have demonstrated a negative impact of the T-cell phenotype on OS. 5,15,16 This may be caused in part by the inclusion of patients with ALCL in the earlier studies.…”
Section: Discussionmentioning
confidence: 91%
“…4 In a subgroup analysis of patients with PTCLu, although patients with AITL had more advanced disease and less bulky masses than those observed in patients with PTCLu, the other characteristics of these patients were similar. Furthermore, the rates of CR/CRu, OS, PFS, and DFS did not Regarding the effect of immunophenotype on patient outcomes, although some earlier studies that were based on the older classification systems reported similar prognoses between patients with Band T-cell lymphomas, [11][12][13][14] most recent studies consistently have demonstrated a negative impact of the T-cell phenotype on OS. 5,15,16 This may be caused in part by the inclusion of patients with ALCL in the earlier studies.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, the disappointing results of CHOP-like regimens [4,55,56,62,64,65,82], demonstrating a limited success of anthracycline-containing regimens, led some groups to investigate alternative approaches, old and new combinations. These include the primary use of platinum-based regimens such as the ESHAP, or very intensive regimens, such as the HyperCVAD [83,84].…”
Section: Treatment Policiesmentioning
confidence: 99%
“…The large intergroup trial comparing CHOP to second and third generation regimens in diffuse large-cell lymphoma failed to reveal any survival differences among the regimens but unfortunately, as immunophenotyping was not widely available at the time of the study analysis, the impact of the specific treatment regimens in the subgroup of patients with T-cell lymphomas was not assessable. 32 Some groups have specifically evaluated more dose-intensive regimens in PTCL 6,[33][34][35] with no firm conclusions demonstrating superiority to CHOP chemotherapy.…”
Section: Primary Treatment Approaches In Ptclsmentioning
confidence: 99%